2007
DOI: 10.1366/000370207779947639
|View full text |Cite
|
Sign up to set email alerts
|

Sequential-Pulse Laser-Induced Breakdown Spectroscopy of High-Pressure Bulk Aqueous Solutions

Abstract: Sequential-pulse (or dual-pulse) laser-induced breakdown spectroscopy (DP-LIBS) with an orthogonal spark orientation is described for elemental analysis of bulk aqueous solutions at pressures up to approximately 138 x 10(5) Pa (138 bar). The use of sequential laser pulses for excitation, when compared to single-pulse LIBS excitation (SP-LIBS), provides significant emission intensity enhancements for a wide range of elements in bulk solution and allows additional elements to be measured using LIBS. Our current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 54 publications
(108 reference statements)
3
42
0
Order By: Relevance
“…The corresponding lines become strong under DP excitation and the maximum enhancement was obtained for Dt = 18 ls. Similar results were reported in [75], where H and Zn lines originating from high excited states were detected only by DP excitation and over a limited range of interpulse delays corresponding to a large, already developed LFB. Systematic measurements of DP LIBS signal as a function of Dt for two collinear beams reveal a complex dependence [85] similar to that shown in Fig.…”
Section: Analysis Of Bulk Liquidssupporting
confidence: 88%
See 2 more Smart Citations
“…The corresponding lines become strong under DP excitation and the maximum enhancement was obtained for Dt = 18 ls. Similar results were reported in [75], where H and Zn lines originating from high excited states were detected only by DP excitation and over a limited range of interpulse delays corresponding to a large, already developed LFB. Systematic measurements of DP LIBS signal as a function of Dt for two collinear beams reveal a complex dependence [85] similar to that shown in Fig.…”
Section: Analysis Of Bulk Liquidssupporting
confidence: 88%
“…For these reasons, DP LIBS losses efficiency at high liquid pressures. The signal enhancement was almost absent above the static pressure of 100 bar for the bubble generated with a laser pulse of 30 mJ [75]. Here, it has been suggested that the pressure range for the LIBS signal enhancement by DP excitation might be achieved by an increase of the first pulse energy or by multi-pulse laser excitation, the both aimed to obtain a larger vapor bubble.…”
Section: Comparison Between Single and Dual Pulse Libs Inside Liquidsmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to overcome those difficulties experienced in liquid analysis, plasma formation on liquid surfaces [3,4], on droplets [5,6], on flowing-jet liquids [7,8] and in cavitation bubbles [9] has been employed. Use of double pulses for plasma formation [10][11][12] has also been realized in liquid analysis by LIBS, with high sensitivity. Aerosol formation by suitable nebulization techniques [13][14][15][16][17][18][19] is another approach to liquid analysis by LIBS.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the highest intensity peaks that are observed occur when two pulses are close together, similar to a single pulse. Lawrence-Snyder et al [30] suggest that at higher solution pressures (8 x 107 Pa), the bubble formed by the first laser pulse is confined by its surrounding pressure. As a result, the bubble never expands to the maximum volume that is observed at lower pressures.…”
mentioning
confidence: 99%